The Impact of Preoperative and Postoperative Malnutrition on Outcomes for Ampullary Carcinoma After Pancreaticoduodenectomy - Jin, Jikuan; Xiong, Guangbing; Wang, Xiaoxiang; Peng, Feng; Zhu, Feng; Wang, Min; Qin, Renyi (Frontiers in Oncology, 2021)
Purpose: The aim of this study was to investigate the effect of preoperative and postoperative malnutrition on postoperative short- and long term outcomes for ampullary carcinoma after pancreatoduodenectomy (PD). Methods: Data were collected retrospectively from 511 patients with ampullary carcinoma underwent PD between June 2012 and June 2019. Nutritional status before and at 3,6 and 12 months after operation was assessed by the scored Patient generated Subjective Global Assessment (PG-SGA). The patients were classified into well-nourished, moderately malnourished and severely malnourished group according to the PG-SGA score. Propensity score matching (PSM) analysis was performed to adjust baseline characteristics between preoperative group A (well-nourished and moderately malnourished group) and group B (severely malnourished group). After PSM, clinicopathological variables, postoperative complications were compared between the two groups. Univariate and multivariate Cox analysis was also conducted to investigate the prognostic factors of overall survival for ampullary carcinoma underwent PD. Results: Preoperatively, 122 (23.9%) patients were classified into well-nourished group, 189 (37.0%) into moderately malnourished group, and 200 (39.1%) into severely malnourished group. After PSM analysis, the incidence of overall postoperative complications was higher in the group B than that in group A (50.5% vs. 32.5%, P<0.001). Multivariate Cox proportional hazards regression model showed the severe malnutrition ( PG-SGA score >9 scores) before operation (HR=1.508, 95% CI: 1.103-2.061; P=0.01), and at 6 months (HR=4.148, 95% CI: 2.523-6.820; P<0.001) and at 12 months (HR=5.272, 95% CI: 3.630-7.656; P<0.001) after operation were independent prognostic factors of patients who underwent PD for ampullary carcinoma. Conclusions: Severe malnutrition before and at 6 and 12 months after operation significantly affect the long-term survival of patients with ampullary carcinoma underwent PD. Additionally, the preoperative malnutrition was closely related to postoperative complications.